The impact of pericytes on the brain and approaches for their morphological analysis - Kolinko, Yaroslav; Kralickova, Milena; Tonar, Zbynek (Journal of chemical neuroanatomy, 2018)
The interest in investigating brain pericytes is growing due to their diverse influences on neuronal function. While numerous studies have investigated the particular properties and functions of pericytes, complex insight into their functional histology is often lacking. In this work, we review and combine the current knowledge regarding brain pericyte function in normal physiology and its role in the pathogenesis of neurodegenerative diseases and tumorigenesis. Special attention is paid to the interaction between the components of the neurovascular unit. Finally, approaches used to detect brain pericytes and the methods for generating qualitative and quantitative data to assess pericyte changes are described.
Keywords: pericyty; mozek; Neurodegeneration; Pericytes; Animals; Histological identify; lidé; Pericyte; Tumor; Humans; zvířata; Brain